Developing Web-Enhanced Physics Learning Media on Renewable Energy Using Google Sites - Agusta, Mutia Velli; Asyhari, Ardian; Mustari, Mukarramah (Jurnal Pijar Mipa, 2025)
Education in Indonesia requires the utilization of technology to improve the quality of learning. The Web-Enhanced Course (WEC) model offers flexibility in accessing learning materials while supporting the effectiveness of face-to-face instruction. Google Sites serves as a relevant medium, integrating text, video, and interactive features that foster students’ motivation and engagement. This study aims to develop physics learning media based on the Web Enhanced Course model using Google Sites, focusing on renewable energy topics, to evaluate its feasibility and assess students’ responses in grade X of senior high schools. This research employed a development method adapted from the Borg and Gall model, which consists of seven stages. Data collection instruments included expert validation sheets for media and material, as well as student response questionnaires. Data were analyzed using descriptive statistical analysis to determine the level of feasibility and attractiveness of the developed media. The results indicated that the physics learning media based on WEC, with the aid of Google Sites, were highly feasible, with material expert validation reaching 85% and media expert validation at 86%. The small-group trial obtained 89%, and the field trial achieved 90%, both categorized as very interesting. Educators and students responded positively to the media in terms of ease of use, material relevance, and engaging presentation. The media has the potential to enhance students’ conceptual understanding of renewable energy and strengthen the integration of digital technology in physics learning. More broadly, this study contributes to the development of 21st-century learning models that are collaborative, interactive, and grounded in digital literacy. Further research is recommended to examine the effectiveness of this media on other physics topics and in diverse educational contexts.